Vegetative tillering plasticity modulates agronomical optimum plant density in winter wheat - Pradella, Luiz Otavio (Kansas State University, 2024)
Agronomic optimum plant density (AOPD) is the minimum number of plants per area required to maximize grain yield. In winter wheat (Triticum aestivum L.), this concept becomes complex due to the tillering trait and its phenotypic variance due to the interaction between genotype and environment (G × E). In this scenario, phenotypic plasticity is an insightful crop ecology perspective to understand G × E. Our objectives were to explore the relations of winter wheat AOPD as a function of environmental and genotypic characteristics in dryland environments from the perspective of phenotypic plasticity. We hypothesize that vegetative tillering phenotypic plasticity is positively correlated with vegetative tiller production and that genotypes with greater vegetative tillering phenotypic plasticity have lower AOPD since greater tiller production may buffer for sub-optimal environmental conditions. A complete factorial experiment evaluated twenty-four wheat varieties seeded at two plant densities (100 and 300 seeds m⁻²) during two seasons in twelve environments. We analyzed the interaction of traits and plant density in a phenotypic plasticity framework. Bayesian hierarchical model was used to estimate grain yield response to plant density and vegetative tillering phenotypic plasticity interaction in a quadratic plateau regression. The effect of vegetative tillering plasticity on the AOPD was evaluated and associated with statistically significant weather variables. Our results demonstrated that beyond the positive effects of the plant density in the traits' phenological response per area, at an individual plant level, traits are affected by plant density in an exponential decay relation, not only for tiller production plant⁻¹, but also for productive tillers per plant⁻¹, spikes plant⁻¹, and grain yield g plant⁻¹. This effect limits the potential of the plant to convert vegetative tillers at high plant densities, not only at individual levels but also at crop levels (productive tillers per area). Vegetative tillering plasticity was positively correlated to vegetative tillering production across plant densities at environments with higher tillering potential, and neutral in lower tillering potential environments. Also, vegetative tillering plasticity was positively related to multiple wheat traits in high-potential environments and was not related to most of the traits' phenotypic expression at lower-potential environments. Overall, winter wheat tillering traits (vegetative and productive) are associated with crop season fall and winter temperature and precipitation. Grain yield with the temperature precipitation and solar radiation experienced during the critical period. On the other hand, the weather variables that lead responsive environments to the vegetative tillering plasticity effect on AOPD (plants m⁻² unit. plasticity⁻¹) are cumulative growing degree days (°C d⁻¹) during winter and grain filling, cumulative precipitation rates (mm) at spring and grain filling, maximum temperatures at winter and grain filling and minimum temperature at spring. Our findings have the following modeling implications, agronomic, and breeding: (i) Seeding rate models and tools, could be improved by accounting for the phenotypic tillering response for a more assertive seeding rate, reducing costs, increasing attainable grain yields, or both. (ii) Under growers' environmental conditions, individual vegetative tillering plasticity may be a tool in the reduction of seed costs, preserving similar yield rates. (iii) Dissecting and stating the genetic basis of winter wheat tillering phenotypic plasticity remains a challenge, as well as their interactions with other management practices.
Keywords: Winter wheat; Vegetative tillering; Agronomical optimum plant density; Phenotypic plasticity